HEALTH ANALYSIS OF SHARIA FINANCING SAVING AND LOAN COOPERATIVES IN PADANG CITY (CASE STUDY OF LUBUK KILANGAN DISTRICT) - M. ZAKY MUBARAK LUBIS; WAHYUNI LELY AUGUSNA; RAMA WAHYUDIN; GUSTI DIRGA ALFAKHRI PUTRA (Universitas Islam Negeri Imam Bonjol Padang, 2021)
This study aims to analyze the soundness level of the Sharia Financing Savings and Loans Cooperative (KSPPS) of Lubuk Begalung District. This descriptive quantitative research uses Perdep No. 07/Per/Dep.06/IV/2016 as a reference for calculating KSPPS health. This research was conducted at 6 KSPPS in Lubuk Begalung District, namely KSPPS Banda Buek, KSPPS Padang Besi, KSPPS Indarung, KSPPS Koto Lalang, KSPPS Tarantang and KSPPS Baringin. The data analyzed is financial report data for 2020. The results showed that of the 6 KSPPS tested, Padang Besi KSPPS received a healthy predicate with a score of 80, 55 and 5 other KSPPS received quite healthy criteria with details of the Banda Buek KSPPS score of 68.1, KSPPS Indarung 77.05, KSPPS Koto Lalang 79.95, KSPPS Baringin 74.35 and KSPPS Tarantang 66.5.